Kontribusi Pelatihan Terhadap Kompetensi Profesional Kerja Guru MAN Se-Kabupaten Aceh Tengah - Sayuti Sayuti (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
This study aims to reveal the contribution of training to the professional competence of MAN teachers in Central Aceh Regency, using descriptive qualitative methods. The study took 15 teachers as respondents, with representatives of each school of 5 teachers including the head of madrasah. This research uses interview techniques by making an interview list, and documentation by attaching teacher certificates that have attended training. This data is used to complement the results of interviews with the research site in obtaining data. The results of this study reveal that; training can help teachers in the learning process to achieve goals, increase their responsibilities and duties as professional teachers after attending training even though they still have not reached the target as expected. Then the madrasah head motivates all teachers to continue their education to a higher level, attend training, such as, Teacher Education and Training (PPG), Teacher Work Stabilization (PKG), Seminars and others in order to improve teachers' professional competence. Teachers are very enthusiastic about attending training, but the quota is limited, so there are still teachers who have never participated in training activities to improve teacher competence, so the madrasah head makes a proposal to the competent party to call teachers who have not attended training.